KAJIAN ONTOLOGIS DAN EPISTEMOLOGIS TENTANG FUNDAMENTALISME DAN RADIKALISME BERAGAMA PERSPEKTIF TEKS SUCI KEAGAMAAN DAN SOSIAL - wasik (EDUTHINK: Jurnal Pemikiran Pendidikan Islam, 2023)
Fundamentalism and radicalism towards contemporary religion are rooted in the Western modernization agenda which failed to reflect the manifestations of modernity. The majority of mutifs originate from perceptions that think that the role of God in fundamentalism and radicalism is threatened and is being replaced by technical progress guidebooks that lead humans to radical socio-cultural-economical changes. Another factor driving the massive development of Islamic society is the failure of modernization, the bad implications of the project of globalization (westernization) of western hegemony and imperialism, and limited industrialization. In this study, a qualitative approach was used in the form of a research library by collecting several books and journal articles in the form of variations.